The crime archives inside the minds of today's deadliest criminals - Wilson, Damon (Carlton Book, 2011)
At once horrifying and fascinating, The Crime Archive is a rogue's gallery of murderers, hitmen, gang leaders, and kidnappers. This gripping foray into the criminal underworld details a variety of offenses--from serial killings to drug smuggling, localized rampages to international headlines. Includes rare facsimiles of documents that led to the capture and conviction of these criminals and more than 100 photographs.